Analisis Pelaksanaan Kegiatan Keagamaan Dimasjid Nurul Islamiyah Sungai Choh Negeri Selangor Malaysia - Rahma, Khodijah; Ridho Saputra, Muhammad; Safitri, Annisah; Latifah, Inayah; Nur Affifah, Najmi; Putri Shabrina, Nadia; Dwi Saputri, Novelly; Setiawan, Evan (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze the implementation of religious activities at the Nurul Islamiyah Mosque in Sungai Choh,Malaysia, during the KKN period. Through in-depth interviews with mosque officials and congregants, this study seeks to understand the types, frequency, and implementation of religious activities at the mosque, as well as the mosque’s role in the surrounding community. The research findings indicate that the Nurul Islamiyah Mosque organizes various religious activities, such as morning lectures, Qur’an completion programs during Ramadan, and preparation for funeral arrangements. Additionally, the mosque plays a central role in building a religious and harmonious community through various social and educational programs. These findings highlight the significance of the mosque as a center of worship and community activities.